2020
DOI: 10.1021/acsnano.0c05398
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photovoltaic Performances of La-Doped Bismuth Ferrite/Zinc Oxide Heterojunction by Coupling Piezo-Phototronic Effect and Ferroelectricity

Abstract: Ferroelectric materials have drawn widespread attention due to their switchable spontaneous polarization and anomalous photovoltaic effect. The coupling between ferroelectricity and the piezo-phototronic effect may lead to the design of distinctive photoelectric devices with multifunctional features. Here, we report an enhancement of the photovoltaic performances in the ferroelectric p-type La-doped bismuth ferrite film (BLFO)/n-type zinc oxide (ZnO) nanowire array heterojunction by rationally coupling the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Surprisingly, among the catalysts, BiVO 4 :I/BTO-Ag showed the highest visible light absorbance intensity, which is beneficial to the improvement of photoreaction efficiency. The energy bandgap was calculated from the absorbance spectra using the Tauc equation: [61]…”
Section: Mechanism For Ros Generationmentioning
confidence: 99%
“…Surprisingly, among the catalysts, BiVO 4 :I/BTO-Ag showed the highest visible light absorbance intensity, which is beneficial to the improvement of photoreaction efficiency. The energy bandgap was calculated from the absorbance spectra using the Tauc equation: [61]…”
Section: Mechanism For Ros Generationmentioning
confidence: 99%
“…Without doping, it is difficult to make up for the shortage of photovoltaic properties of ferroelectric materials. Another way to improve the performance of ferroelectric photovoltaic devices is to combine ferroelectric materials with other materials such as semiconductors [97][98][99][100] Heterojunctions are formed when ferroelectric materials and semiconductor materials come into contact, and the built-in electric field corresponding to formation. The built-in electric field can effectively separate carriers, producing excellent photovoltaic performance externally.…”
Section: Combine With Other Materialsmentioning
confidence: 99%
“…The most representative semiconductor materials for ferroelectric photovoltaic devices are n-type ZnO and p-type CuO materials. [97,[101][102][103][104][105] It has been shown that photovoltaic devices based on ZnO/BFO heterojunctions exhibited much larger photocurrent than devices based on individual ZnO or BFO. [101,104,106] One of the reasons for this phenomenon is that ZnO has a high internal electron mobility compared to ferroelectric materials.…”
Section: Combine With Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al ( 2020) [36] investigated the piezophototronic effect on La-doped BFO/ZnO heterojunction and observed that rise time of ZnO significantly modulated from 153.7 ms to 61.28 ms. In this study they used la-doped BFO as p-type film and ZnO as n-type film.…”
Section: Heterostructure Based Solar Cellsmentioning
confidence: 99%